2012
DOI: 10.1186/ar4100
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory effect of IL-21 on T follicular helper-like cell and B cell in rheumatoid arthritis

Abstract: IntroductionInterleukin (IL)-21 is a member of type I cytokine family. Recent studies indicate that IL-21 can promote T follicular helper (Tfh) cell differentiation and survival, a specialized T cell subset which provides help for B cell. It can also regulate the activation, proliferation and differentiation of human B cell and immunoglobulin (Ig) production as well as isotype switching of plasma cell. Rheumatoid arthritis (RA) is characterized by auto-antibodies overproduction such as rheumatoid factor (RF) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 45 publications
(49 reference statements)
9
115
1
2
Order By: Relevance
“…We found that the levels of serum IL-21 were significantly higher in the RA patients than that in the HC. These results were in agreement with a previous observation showing that IL-21 regulates Tfh and B cell function [41]. We are interested in investigating further how IL-21 regulates B and Tfh cell activation and differentiation in RA patients.…”
Section: Tfh and Cd95supporting
confidence: 81%
“…We found that the levels of serum IL-21 were significantly higher in the RA patients than that in the HC. These results were in agreement with a previous observation showing that IL-21 regulates Tfh and B cell function [41]. We are interested in investigating further how IL-21 regulates B and Tfh cell activation and differentiation in RA patients.…”
Section: Tfh and Cd95supporting
confidence: 81%
“…Similarly, the percentages of circulating PD-1 + CD4 + CXCR5 + and ICOS + CD4 + CXCR5 + are significantly higher in RA patients than in healthy controls [3]. Furthermore, the concentrations of serum IL-21 in RA patients are significantly higher than that in healthy controls [25]. Functionally, circulating TFH cells can be divided into three subsets [22,23].…”
Section: Circulating Tfh Cellsmentioning
confidence: 94%
“…Supporting the role of TFHs in the generation of GC, we demonstrated that TFHs were the major source of IL-21 in ITP spleen, a key cytokine involved in B-cell stimulation and differentiation. 42 44 has been demonstrated and has justified the use of anti-IL-21 therapy in clinical trials. 45 However, the fact that bone marrow PCs, contrary to secondary lymphoid organ PCs, do not depend on IL-21 to survive, 46 argues for a blockade of the IL-21 axis early in the disease, before the establishment of long-lived PCs.…”
Section: Discussionmentioning
confidence: 99%